Legal Aid Days as a Research Tool : Experiences from Northern Kenya - Ayuko, Bonita (World Bank, Washington, DC, 2018)
Providing legal aid as part of a research program can bring both methodological and community benefits. Legal aid days encourage people to open up more quickly, increase the amount of information people are willing to share, enable less vocal members of the community to speak out and satisfy the desire of researchers to give something back to communities - rather than just extract information. Since 2007, the World Bank's justice for the poor program has been partnering with the Legal Resource Foundation (LRF), a Kenyan non-government organization (NGO), working to implement field research in the arid lands region of Northern Kenya. Together, they seek to understand how the poor and marginalized navigate prevailing justice systems. Legal aid days were included as part of the research methodology, capitalizing on LRF's wealth of experience in the legal aid sector.